2020
DOI: 10.1109/access.2020.3019631
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation Framework for Assessing the Impact of Location Privacy on Geospatial Analysis

Abstract: The need for addressing geoprivacy in location based services has increased the offer of mechanisms that protect location information, however, these algorithms are not always developed to ensure the usability of the data and therefore, their adoption is not wide. In this work, a framework is presented to evaluate the effects of geoprivacy mechanisms on the quality of geodata to provide insights into how the data is affected for geospatial analysis. For this purpose, a toolkit of indices was developed to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
5
13
0
Order By: Relevance
“…These results are consistent with those obtained by Zurbaran et al. (2020), who applied the Pinwheel method with 30° and 100° on crime data. However, just based on the comparison of two angles, a definite conclusion may not be accurate.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are consistent with those obtained by Zurbaran et al. (2020), who applied the Pinwheel method with 30° and 100° on crime data. However, just based on the comparison of two angles, a definite conclusion may not be accurate.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with the findings of Zurbaran et al. (2020), who showed that the density‐based NRand‐ k method outperformed a handful of other methods in terms of spatial pattern preservation, followed by the Pinwheel and Donut methods applied on crime data. Similarly, Zurbarán et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[88,98] Used encryption to hideTMSI ■TMSI is hiding ■Auth. message size did not change ■Communication overhead is high ■Computation complexity is high ■It contains the TMSI if the attack gets it [1, 84, 97, 98] Used either expired time, encryption C-RNTI or LBE in LBS ■The location is encrypted ■Communication overhead is high ■Computation complexity is high ■C-RNTI.…”
mentioning
confidence: 99%